2011
DOI: 10.1111/j.1756-185x.2011.01632.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated production of galectin-3 is correlated with juvenile idiopathic arthritis disease activity, severity, and progression

Abstract: These results suggest that serum levels of galectin-3 are increased in active JIA children and galectin-3 can be a new biomarker indicating JIA disease activity, severity and progression, although its increment is not disease-specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 19 publications
2
27
0
1
Order By: Relevance
“…The results of our study were comparable with those reported in literature. Previous studies documented the changed levels of galectin-3 in patients with RA, juvenile idiopathic arthritis (JIA), SSc, ankylosing spondylitis (AS) or Behcet's diseases (BD) [6,[21][22][23][24]. For example, Ohshima et al has demonstrated increased levels of galectin-3 both in RA synovial uid and serum in comparison to patients with osteoarthritis and healthy subjects [6].…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study were comparable with those reported in literature. Previous studies documented the changed levels of galectin-3 in patients with RA, juvenile idiopathic arthritis (JIA), SSc, ankylosing spondylitis (AS) or Behcet's diseases (BD) [6,[21][22][23][24]. For example, Ohshima et al has demonstrated increased levels of galectin-3 both in RA synovial uid and serum in comparison to patients with osteoarthritis and healthy subjects [6].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study of plasma galectin‐3 showed increased concentrations in septicaemia but not in viral infections or in attacks of nondetermined autoinflammatory syndromes, as compared to healthy controls . The increase of galectin‐3 in several other inflammatory conditions has been reported, including systemic lupus erythematosus (SLE) , Behçet's disease and juvenile idiopathic arthritis , as well as in Crohn's disease and ulcerative colitis . If the findings of increased plasma levels of galectin‐3 in other inflammatory diseases and low levels in PFAPA are verified, galectin‐3 might be used as tool to distinguish these conditions from PFAPA, particularly with regard to young children who originate in regions with a high prevalence of FMF.…”
Section: The Continuum Model Of Immunological Diseasesmentioning
confidence: 94%
“…Hence, the proposed Galectin-3 binding to lubricin 32 are likely to only fine-tune the boundary lubricating glycosurface of the joint. In regards of galectin-3 level in SF, it has also been shown that patients with RA have increased level of galectin-3 46,47,48 , while the literature is less conclusive about the situation in OA. Our data shows that compared to the normal SF, the galectin-3 levels are diminished in late stage OA.…”
Section: Truncation Of Sf Lubricin O-glycosylation In Oa and Galectin-3mentioning
confidence: 99%